Pressure induced rhabdomyolysis complicating an undiscovered fall. - Ratcliffe, P; Berman, P; Griffiths, R (1983)
An 82-year-old man developed severe pressure-induced rhabdomyolysis after falling and remaining undiscovered on the floor. This unusually severe case is reported to illustrate the features of a condition which in milder degree may be common in old people and give rise to diagnostic confusion.